Stress and Coping Strategies among Parents of Preterm Infants Admitted to Three Hospitals in Nepal - Shrestha, Tumla; Bista, Archana Pandey; Subedi, Madhusudan (Europasian Journal of Medical Sciences, 2023)
Background Hospitalization in neonatal care units (NCUs) is distressing to parents. Stress and inadequate coping hinder parents’ emotional health and parenting roles. Furthermore, it may impact short- and long-term developmental, cognitive, academic, and mental health outcomes among preterm infants (PTIs). This study aimed to explore the stress and coping mechanisms adopted by parents in NCUs. Data and Methods The descriptive phenomenological study was conducted in the NCUs of three public tertiary hospitals in Kathmandu, Nepal. In-depth interviews were conducted with 15 purposively selected parents, both mothers and fathers, of preterm and low birth weight infants admitted to the NCUs. The data were descriptively analyzed employing the Colaizzi method to elucidate the stress experiences and coping strategies of parents. Results The exploration of parents’ experiences yielded two overarching themes, namely psychological distress and insecurity and coping with the support system. Parents’ distress was linked to PTIs’ condition, infant–parent separation, altered parenting roles, and prolonged hospitalization. Family, friends, peer parents, and NCU staff were parents’ support sources. They coped with the situation by sharing experiences with peer parents, fostering closeness with the PTIs, and actively involving in care. Conclusion Admission of PTIs to NCUs was distressing to parents. Parents valued NCU staff’s support for coping and expected more support. The provision of free newborn care service is pivotal in alleviating financial burden. Opportunities for fostering infant–parent attachment, active care involvement, and peer-to-peer support are effective coping measures for parents. Improving parental support provision in NCUs considering this stress and coping mechanisms would enhance psychological well-being of parents.